High-strength PVC waterproof coiled material and preparation method thereof
By introducing polyvinylidene fluoride and composite modified nano-silica into PVC waterproof rolls and adopting hot press composite technology, the problem of insufficient strength and aging resistance of ordinary PVC waterproof rolls is solved, and high strength and durability are achieved Sexy waterproof effect.
Patent Information
- Application Number
- CN202411357362.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-09-27
AI Technical Summary
Ordinary PVC waterproof coils are not strong enough, and their aging resistance is not good enough. They are easily damaged in harsh environments, resulting in a weakening of the waterproof effect.
By introducing polyvinylidene fluoride and composite modified nanosilicon dioxide into the PVC waterproof coil, and using a hot pressing composite process, a high-strength PVC waterproof coil was prepared. The method includes arranging the polyester cloth, polyvinyl chloride coil and glass fiber mesh cloth in order, hot pressing composite at 145 to 180°C, and cooling to obtain a high-strength PVC waterproof coil.
It significantly improves the mechanical properties, thermal stability, chemical corrosion resistance and aging resistance of PVC waterproof coils, making them more durable and waterproof in harsh environments.
Smart Images

Figure BDA0005064005350000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of waterproof coiled materials, in particular to a high-strength PVC waterproof coiled material and a preparation method thereof. Background Art
[0002] Waterproofing of building construction has always been an inevitable problem for designers and constructors. The common solution to this problem is to use waterproofing membranes or waterproof coatings. Compared with waterproof coatings, waterproofing membranes have the advantages of being suitable for large-scale laying, no maintenance required after forming, and uniform thickness of waterproof layer. Polyvinyl chloride (PVC) waterproofing membrane is a polymer waterproofing membrane with polyvinyl chloride resin as the main raw material. It has the characteristics of high elongation, small shrinkage, long service life, stable product performance, and convenient construction. It is used in harsh environments such as tunnels, highways, viaducts and landfills. However, ordinary PVC waterproofing membranes are not strong enough and have poor aging resistance. They are easily damaged in these harsh environments, resulting in a weakening of the waterproofing effect. Therefore, it is necessary to develop PVC waterproofing membranes with higher strength and better aging resistance. Summary of the invention
[0003] The purpose of the present invention is to provide a high-strength PVC waterproof coiled material and a preparation method thereof, so as to solve the problem that the strength of ordinary PVC waterproof coiled materials is not high enough and the aging resistance is not good enough.
[0004] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0005] A method for preparing a high-strength PVC waterproof coiled material, characterized in that the preparation method comprises:
[0006] After arranging the polyester cloth, polyvinyl chloride coil and glass fiber mesh cloth in sequence, they are hot-pressed and compounded at 145-180° C., and after cooling to room temperature, a high-strength PVC waterproof coil is obtained.
[0007] As a limitation of the present invention, the preparation method of the polyvinyl chloride coil is:
[0008] Polyvinyl chloride, polyvinylidene fluoride, composite modified nano-silica and additives are mixed, extruded through an extruder, and calendered, pulled and rolled to prepare a polyvinyl chloride coil. During the extrusion, the mixing temperature is 70-90°C, the extrusion temperature is 170-190°C, and the screw speed is 10-30rpm.
[0009] As a limitation of the present invention, the preparation method of the composite modified nano-silicon dioxide is:
[0010] The nano-silicon dioxide and toluene are mixed in a mass ratio of 1:(24-26), and ultrasonically dispersed for 20-40 minutes to obtain a nano-silicon dioxide dispersion, the nano-silicon dioxide dispersion is mixed with 3-aminopropyltriethoxysilane, and the mixture is reacted at 90-100° C. for 14-16 hours under nitrogen as a protective gas, cooled, and filtered to obtain a solid, and the solid is washed with toluene, and vacuum dried at 55-65° C. to obtain amino-modified nano-silicon dioxide;
[0011] 2-bromoisobutyryl bromide and toluene are mixed in a mass ratio of (3.8-4.0):(4.1-4.3) to obtain a 2-bromoisobutyryl bromide solution, and amination nano-silica, toluene, triethylamine and the 2-bromoisobutyryl bromide solution are mixed, and the mixture is reacted at -5-0°C for 2-4 hours under nitrogen as a protective gas, and the mixture is heated to 25-30°C and the reaction is continued for 11-13 hours. After the reaction is completed, the mixture is filtered, washed with acetone and water, and vacuum dried at 55-65°C to obtain brominated nano-silica;
[0012] The invention relates to a method for preparing a composite modified nano-silica. The method comprises the following steps: mixing 0.57-0.59 parts of ferric chloride hexahydrate, 4.2-4.3 parts of triphenylphosphine, 4.9-5.1 parts of brominated nano-silica, 188-190 parts of N,N-dimethylformamide and 178-180 parts of butyl acrylate, and performing ultrasonic dispersion for 14-16 minutes under closed conditions to form a mixed solution. The mixed solution is added with 1-1.1 parts of ascorbic acid, and the mixture is kept closed and reacted at 85-95° C. for 7-9 hours. The mixture is cooled, filtered, washed with tetrahydrofuran, and vacuum dried to obtain polybutyl acrylate-brominated nano-silica. The polybutyl acrylate-brominated nano-silica, triethylamine, mercaptoethylamine and tetrahydrofuran are mixed, reacted at 25-30° C. and 50-70 rpm for 7-9 hours, filtered, washed with methanol and water, and vacuum dried to obtain a composite modified nano-silica.
[0013] As a limitation of the present invention, the preparation method of the auxiliary agent is:
[0014] By weight, 2 to 4 parts of talc, 1 to 3 parts of paraffin, 6 to 8 parts of antioxidant, 27 to 29 parts of plasticizer, and 9 to 11 parts of lead stearate are uniformly mixed to obtain an auxiliary agent.
[0015] As a limitation of the present invention, the mass ratio of the polyvinyl chloride, polyvinylidene fluoride, composite modified nano-silica and additives is (71-73):(15-17):(7-9):(3-5).
[0016] As a limitation of the present invention, the mass ratio of the nano-silicon dioxide dispersion to 3-aminopropyltriethoxysilane is (25-27):(1.8-2.0).
[0017] As a limitation of the present invention, the mass ratio of the amino-modified nano-silica, toluene, triethylamine and 2-bromoisobutyryl bromide solution is 1:(12.4-12.6):(1.45-1.46):(8.0-8.2).
[0018] As a limitation of the present invention, the mass ratio of the polybutyl acrylate-brominated nano-silica, triethylamine, mercaptoethylamine and tetrahydrofuran is (9.9-10.1):(0.14-0.16):(0.11-0.13):(177-179).
[0019] The beneficial effects achieved by the present invention are:
[0020] Polyvinylidene fluoride has excellent mechanical properties, thermal stability, chemical corrosion resistance and aging resistance, and can significantly enhance its performance after being blended with PVC. However, the two have poor compatibility, while polybutyl acrylate has good compatibility with both, which can make polyvinylidene fluoride more evenly dispersed in the composite material.
[0021] Nano-silica is an inorganic non-metallic material with excellent UV resistance, mechanical properties and chemical stability, and can be used to improve polymers. However, nano-silica has good hydrophilicity and poor compatibility with polymers, so it is necessary to modify nano-silica. Common modification methods include grafting groups with good compatibility with polymers on the surface of particles. Although it can improve the dispersion of inorganic particles in polymers to a certain extent, it still cannot achieve a uniform dispersion effect. The core-shell structure of inorganic particles coated with organic polymers can achieve uniform dispersion of inorganic particles in polymers, thereby improving the comprehensive performance of composite materials.
[0022] Core-shell nanoparticles with rigid nano-silica as the core and flexible polybutyl acrylate as the shell. Polybutyl acrylate contains a large number of ester groups that can interact with PVC and have good miscibility with PVC. Nano-silica and polybutyl acrylate are combined together through strong chemical reactions, which can effectively enhance the strength and toughness of the composite material. In addition, when PVC ages, HCl will be removed at structural defects. The removed HCl catalyzes the rearrangement of hydrogen to form new active centers, and HCl will continue to be removed, thereby accelerating the aging of the material. Through the reaction of triethylamine with bromine on the surface of the core-shell nanoparticles, the bromine on the outer layer of the core-shell structure is replaced by amino groups, and core-shell nanoparticles with amino groups on the surface are obtained. The amino groups on the surface can effectively bind to the HCl removed by PVC aging, preventing the material from further aging. DETAILED DESCRIPTION
[0023] The following is a preferred implementation of the embodiment of the present invention. Obviously, the described embodiment is only a part of the embodiment of the present invention, not all of the embodiments. For ordinary technicians in this technical field, all other embodiments obtained by ordinary technicians in this field without creative work without departing from the principle of the embodiment of the present invention are within the scope of protection of the present invention.
[0024] Nano-silicon dioxide (P-0447182), talc (R000973), paraffin (R002109), antioxidant 1010 (R150166), and plasticizer DOP (R004097) were provided by Shanghai Yien, polyvinyl chloride (P-0447182) and polyvinylidene fluoride (P-85140) were provided by Tianjin Xiensi, polyester cloth (thickness 0.8-1.2 mm) was provided by Hejian Zhengtu Hongtai, and glass fiber mesh cloth (80-100 g / m 2 ) is provided by Anping County Chuanhang Wire Mesh Products.
[0025] Embodiment 1: A method for preparing a high-strength PVC waterproofing coiled material, specifically:
[0026] Step 1: Preparation of amino-modified nano-silica
[0027] Nano-silica and toluene were mixed in a mass ratio of 1:25, and ultrasonically dispersed for 30 minutes to obtain a nano-silica dispersion. The nano-silica dispersion was mixed with 3-aminopropyltriethoxysilane in a mass ratio of 26:1.9, and reacted at 95° C. for 15 hours under nitrogen as a protective gas. The solid was cooled and filtered to obtain a solid. The solid was washed with toluene and vacuum dried at 60° C. to obtain amino-nano-silica.
[0028] Step 2: Preparation of brominated nanosilica
[0029] 2-Bromoisobutyryl bromide and toluene are mixed in a mass ratio of (3.8-4.0):(4.1-4.3) to obtain a 2-bromoisobutyryl bromide solution; amino-modified nano-silica, toluene, triethylamine and 2-bromoisobutyryl bromide solution are mixed in a mass ratio of 1:12.5:1.455:8.1; the mixture is reacted at -2°C for 3 hours under nitrogen as protective gas, the temperature is raised to 27°C, and the reaction is continued for 12 hours. After the reaction is completed, the mixture is filtered, washed with acetone and water, and dried in vacuo at 60°C to obtain brominated nano-silica.
[0030] Step 3: Preparation of composite modified nano-silica
[0031] By mass, 0.58 parts of ferric chloride hexahydrate, 4.25 parts of triphenylphosphine, 5.0 parts of brominated nano-silica, 189 parts of N,N-dimethylformamide, and 179 parts of butyl acrylate were mixed, and ultrasonically dispersed for 15 minutes under closed conditions to form a mixed solution. 1.05 parts of ascorbic acid were added to the mixed solution, which was kept sealed and reacted at 90°C for 8 hours. The mixture was cooled, filtered, washed with tetrahydrofuran, and vacuum dried to obtain polybutyl acrylate-brominated nano-silica. Polybutyl acrylate-brominated nano-silica, triethylamine, mercaptoethylamine and tetrahydrofuran were mixed in a mass ratio of 10:0.15:0.12:178, reacted at 27°C and 60rpm for 8 hours, filtered, washed with methanol and water, and vacuum dried to obtain composite modified nano-silica.
[0032] Step 4: Prepare the additive
[0033] By weight, 3 parts of talc, 2 parts of paraffin, 7 parts of antioxidant 1010, 28 parts of plasticizer DOP, and 10 parts of lead stearate were uniformly mixed to obtain an auxiliary agent.
[0034] Step 5: Prepare the PVC membrane
[0035] Polyvinyl chloride, polyvinylidene fluoride, composite modified nano-silica and additives are mixed in a mass ratio of 72:16:8:4, and the mixture is extruded through an extruder. The mixture is calendered, pulled and rolled to prepare a polyvinyl chloride coil. The process conditions for the extrusion are as follows: the temperature during mixing is 80°C, the temperature in the extruder is 180°C, and the screw speed is 20rpm.
[0036] Step 6: Prepare high-strength PVC waterproof membrane
[0037] After arranging the polyester cloth, polyvinyl chloride coil and glass fiber mesh cloth in sequence, they are hot-pressed and compounded at 160° C., and after cooling to room temperature, a high-strength PVC waterproof coil is obtained.
[0038] Embodiment 2: A method for preparing a high-strength PVC waterproofing membrane, specifically:
[0039] Step 1: Preparation of amino-modified nano-silica
[0040] Nano-silica and toluene were mixed in a mass ratio of 1:25, and ultrasonically dispersed for 30 minutes to obtain a nano-silica dispersion. The nano-silica dispersion was mixed with 3-aminopropyltriethoxysilane in a mass ratio of 26:1.9, and reacted at 95° C. for 15 hours under nitrogen as a protective gas. The solid was cooled and filtered to obtain a solid. The solid was washed with toluene and vacuum dried at 60° C. to obtain amino-nano-silica.
[0041] Step 2: Preparation of brominated nanosilica
[0042] 2-Bromoisobutyryl bromide and toluene are mixed in a mass ratio of (3.8-4.0):(4.1-4.3) to obtain a 2-bromoisobutyryl bromide solution; amino-modified nano-silica, toluene, triethylamine and 2-bromoisobutyryl bromide solution are mixed in a mass ratio of 1:12.5:1.455:8.1; the mixture is reacted at -2°C for 3 hours under nitrogen as protective gas, the temperature is raised to 27°C, and the reaction is continued for 12 hours. After the reaction is completed, the mixture is filtered, washed with acetone and water, and dried in vacuo at 60°C to obtain brominated nano-silica.
[0043] Step 3: Preparation of composite modified nano-silica
[0044] By mass, 0.58 parts of ferric chloride hexahydrate, 4.25 parts of triphenylphosphine, 5.0 parts of brominated nano-silica, 189 parts of N,N-dimethylformamide, and 179 parts of butyl acrylate were mixed, and ultrasonically dispersed for 15 minutes under closed conditions to form a mixed solution. 1.05 parts of ascorbic acid were added to the mixed solution, which was kept sealed and reacted at 90°C for 8 hours. The mixture was cooled, filtered, washed with tetrahydrofuran, and vacuum dried to obtain polybutyl acrylate-brominated nano-silica. Polybutyl acrylate-brominated nano-silica, triethylamine, mercaptoethylamine and tetrahydrofuran were mixed in a mass ratio of 9.9:0.14:0.11:177, reacted at 27°C and 60rpm for 8 hours, filtered, washed with methanol and water, and vacuum dried to obtain composite modified nano-silica.
[0045] Step 4: Prepare the additive
[0046] By weight, 3 parts of talc, 2 parts of paraffin, 7 parts of antioxidant 1010, 28 parts of plasticizer DOP, and 10 parts of lead stearate were uniformly mixed to obtain an auxiliary agent.
[0047] Step 5: Prepare the PVC membrane
[0048] Polyvinyl chloride, polyvinylidene fluoride, composite modified nano-silica and additives are mixed in a mass ratio of 71:15:7:3, and the mixture is extruded through an extruder. The mixture is calendered, pulled and rolled to prepare a polyvinyl chloride coil. The process conditions for the extrusion are as follows: the temperature during mixing is 80°C, the temperature in the extruder is 180°C, and the screw speed is 20rpm.
[0049] Step 6: Prepare high-strength PVC waterproof membrane
[0050] After arranging the polyester cloth, polyvinyl chloride coil and glass fiber mesh cloth in sequence, they are hot-pressed and compounded at 160° C., and after cooling to room temperature, a high-strength PVC waterproof coil is obtained.
[0051] Embodiment 3: A method for preparing a high-strength PVC waterproofing coiled material, specifically:
[0052] Step 1: Preparation of amino-modified nano-silica
[0053] Nano-silica and toluene were mixed in a mass ratio of 1:25, and ultrasonically dispersed for 30 minutes to obtain a nano-silica dispersion. The nano-silica dispersion was mixed with 3-aminopropyltriethoxysilane in a mass ratio of 26:1.9, and reacted at 95° C. for 15 hours under nitrogen as a protective gas. The solid was cooled and filtered to obtain a solid. The solid was washed with toluene and vacuum dried at 60° C. to obtain amino-nano-silica.
[0054] Step 2: Preparation of brominated nanosilica
[0055] 2-Bromoisobutyryl bromide and toluene are mixed in a mass ratio of (3.8-4.0):(4.1-4.3) to obtain a 2-bromoisobutyryl bromide solution; amino-modified nano-silica, toluene, triethylamine and 2-bromoisobutyryl bromide solution are mixed in a mass ratio of 1:12.5:1.455:8.1; the mixture is reacted at -2°C for 3 hours under nitrogen as protective gas, the temperature is raised to 27°C, and the reaction is continued for 12 hours. After the reaction is completed, the mixture is filtered, washed with acetone and water, and dried in vacuo at 60°C to obtain brominated nano-silica.
[0056] Step 3: Preparation of composite modified nano-silica
[0057] By mass, 0.58 parts of ferric chloride hexahydrate, 4.25 parts of triphenylphosphine, 5.0 parts of brominated nano-silica, 189 parts of N,N-dimethylformamide, and 179 parts of butyl acrylate were mixed, and ultrasonically dispersed for 15 minutes under closed conditions to form a mixed solution. 1.05 parts of ascorbic acid were added to the mixed solution, which was kept sealed and reacted at 90°C for 8 hours. The mixture was cooled, filtered, washed with tetrahydrofuran, and vacuum dried to obtain polybutyl acrylate-brominated nano-silica. Polybutyl acrylate-brominated nano-silica, triethylamine, mercaptoethylamine and tetrahydrofuran were mixed in a mass ratio of 10.1:0.16:0.13:179, reacted at 27°C and 60rpm for 8 hours, filtered, washed with methanol and water, and vacuum dried to obtain composite modified nano-silica.
[0058] Step 4: Prepare the additive
[0059] By weight, 3 parts of talc, 2 parts of paraffin, 7 parts of antioxidant 1010, 28 parts of plasticizer DOP, and 10 parts of lead stearate were uniformly mixed to obtain an auxiliary agent.
[0060] Step 5: Prepare the PVC membrane
[0061] Polyvinyl chloride, polyvinylidene fluoride, composite modified nano-silica and additives are mixed in a mass ratio of 73:17:9:5, and the mixture is extruded through an extruder. The mixture is calendered, pulled and rolled to prepare a polyvinyl chloride coil. The process conditions for the extrusion are as follows: the temperature during mixing is 80°C, the temperature in the extruder is 180°C, and the screw speed is 20rpm.
[0062] Step 6: Prepare high-strength PVC waterproof membrane
[0063] After arranging the polyester cloth, polyvinyl chloride coil and glass fiber mesh cloth in sequence, they are hot-pressed and compounded at 160° C., and after cooling to room temperature, a high-strength PVC waterproof coil is obtained.
[0064] Based on Example 1, control experiments were carried out, specifically Comparative Example 1, Comparative Example 2 and Comparative Example 3, as described below:
[0065] Comparative Example 1: The nano-silicon dioxide was not treated, and the other conditions were the same as those in Example 1.
[0066] A method for preparing a high-strength PVC waterproof coiled material, specifically comprising:
[0067] Step 1: Prepare the additive
[0068] By weight, 3 parts of talc, 2 parts of paraffin, 7 parts of antioxidant 1010, 28 parts of plasticizer DOP, and 10 parts of lead stearate were uniformly mixed to obtain an auxiliary agent.
[0069] Step 2: Prepare the PVC membrane
[0070] Polyvinyl chloride, polyvinylidene fluoride, nano-silica and additives are mixed in a mass ratio of 72:16:8:4, and the mixture is extruded through an extruder. The mixture is calendered, pulled and rolled to prepare a polyvinyl chloride coil. The process conditions of the extrusion are as follows: the temperature during mixing is 80°C, the temperature in the extruder is 180°C, and the screw speed is 20rpm.
[0071] Step 3: Prepare high-strength PVC waterproof membrane
[0072] After arranging the polyester cloth, polyvinyl chloride coil and glass fiber mesh cloth in sequence, they are hot-pressed and compounded at 160° C., and after cooling to room temperature, a high-strength PVC waterproof coil is obtained.
[0073] Comparative Example 2: Aminated nano-silica was used, and the other conditions were the same as those in Example 1.
[0074] A method for preparing a high-strength PVC waterproof coiled material, specifically comprising:
[0075] Step 1: Preparation of amino-modified nano-silica
[0076] Nano-silica and toluene were mixed in a mass ratio of 1:25, and ultrasonically dispersed for 30 minutes to obtain a nano-silica dispersion. The nano-silica dispersion was mixed with 3-aminopropyltriethoxysilane in a mass ratio of 26:1.9, and reacted at 95° C. for 15 hours under nitrogen as a protective gas. The solid was cooled and filtered to obtain a solid. The solid was washed with toluene and vacuum dried at 60° C. to obtain amino-nano-silica.
[0077] Step 2: Prepare the additive
[0078] By weight, 3 parts of talc, 2 parts of paraffin, 7 parts of antioxidant 1010, 28 parts of plasticizer DOP, and 10 parts of lead stearate were uniformly mixed to obtain an auxiliary agent.
[0079] Step 3: Prepare the PVC membrane
[0080] Polyvinyl chloride, polyvinylidene fluoride, amino-modified nano-silica and additives are mixed in a mass ratio of 72:16:8:4, and the mixture is extruded through an extruder. The mixture is calendered, pulled and rolled to prepare a polyvinyl chloride coil. The process conditions of the extrusion are as follows: the temperature during mixing is 80°C, the temperature in the extruder is 180°C, and the screw speed is 20rpm.
[0081] Step 4: Prepare high-strength PVC waterproof membrane
[0082] After arranging the polyester cloth, polyvinyl chloride coil and glass fiber mesh cloth in sequence, they are hot-pressed and compounded at 160° C., and after cooling to room temperature, a high-strength PVC waterproof coil is obtained.
[0083] Comparative Example 3: No polyvinylidene fluoride was blended, and other conditions were the same as those in Example 1.
[0084] A method for preparing a high-strength PVC waterproof coiled material, specifically comprising:
[0085] Step 1: Preparation of amino-modified nano-silica
[0086] Nano-silica and toluene were mixed in a mass ratio of 1:25, and ultrasonically dispersed for 30 minutes to obtain a nano-silica dispersion. The nano-silica dispersion was mixed with 3-aminopropyltriethoxysilane in a mass ratio of 26:1.9, and reacted at 95° C. for 15 hours under nitrogen as a protective gas. The solid was cooled and filtered to obtain a solid. The solid was washed with toluene and vacuum dried at 60° C. to obtain amino-nano-silica.
[0087] Step 2: Preparation of brominated nanosilica
[0088] 2-Bromoisobutyryl bromide and toluene are mixed in a mass ratio of (3.8-4.0):(4.1-4.3) to obtain a 2-bromoisobutyryl bromide solution; amino-modified nano-silica, toluene, triethylamine and 2-bromoisobutyryl bromide solution are mixed in a mass ratio of 1:12.5:1.455:8.1; the mixture is reacted at -2°C for 3 hours under nitrogen as protective gas, the temperature is raised to 27°C, and the reaction is continued for 12 hours. After the reaction is completed, the mixture is filtered, washed with acetone and water, and dried in vacuo at 60°C to obtain brominated nano-silica.
[0089] Step 3: Preparation of composite modified nano-silica
[0090] By mass, 0.58 parts of ferric chloride hexahydrate, 4.25 parts of triphenylphosphine, 5.0 parts of brominated nano-silica, 189 parts of N,N-dimethylformamide, and 179 parts of butyl acrylate were mixed, and ultrasonically dispersed for 15 minutes under closed conditions to form a mixed solution. 1.05 parts of ascorbic acid were added to the mixed solution, which was kept sealed and reacted at 90°C for 8 hours. The mixture was cooled, filtered, washed with tetrahydrofuran, and vacuum dried to obtain polybutyl acrylate-brominated nano-silica. Polybutyl acrylate-brominated nano-silica, triethylamine, mercaptoethylamine and tetrahydrofuran were mixed in a mass ratio of 10:0.15:0.12:178, reacted at 27°C and 60rpm for 8 hours, filtered, washed with methanol and water, and vacuum dried to obtain composite modified nano-silica.
[0091] Step 4: Prepare the additive
[0092] By weight, 3 parts of talc, 2 parts of paraffin, 7 parts of antioxidant 1010, 28 parts of plasticizer DOP, and 10 parts of lead stearate were uniformly mixed to obtain an auxiliary agent.
[0093] Step 5: Prepare the PVC membrane
[0094] Polyvinyl chloride, composite modified nano-silica and additives are mixed in a mass ratio of 72:8:4, and the mixture is extruded through an extruder. The mixture is calendered, pulled and rolled to prepare a polyvinyl chloride coil. The process conditions for the extrusion are as follows: the temperature during mixing is 80°C, the temperature in the extruder is 180°C, and the screw speed is 20rpm.
[0095] Step 6: Prepare high-strength PVC waterproof membrane
[0096] After arranging the polyester cloth, polyvinyl chloride coil and glass fiber mesh cloth in sequence, they are hot-pressed and compounded at 160° C., and after cooling to room temperature, a high-strength PVC waterproof coil is obtained.
[0097] Detection experiment:
[0098] Polyvinyl chloride coils were prepared according to the preparation methods in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, and Comparative Example 3, respectively, and placed in an environment with a temperature of 23° C. and a relative humidity of 60% for 24 hours.
[0099] Mechanical properties test: The test was conducted in accordance with "Polyvinyl chloride (PVC) waterproof membrane" (GB / T 12592-2011). 150mm×50mm specimens were cut from the waterproof membrane prepared above, and the specimens were fixed on the furniture of the tensile testing machine. The tensile testing machine was used to test each specimen in turn, and the tensile strength and elongation at break of each specimen were measured.
[0100] Water absorption test: the test was conducted in accordance with "Polyvinyl chloride (PVC) waterproof membrane" (GB / T 12592-2011). Samples of 100 mm × 70 mm were cut out from the waterproof membrane prepared above, and each sample was weighed after being dried for 24 hours. Then, each sample was soaked in 70°C distilled water for 168 hours, taken out, and put into 23°C distilled water for 15 minutes. The water marks on the surface of the sample were immediately wiped off, and the weight of each sample was weighed again to calculate the water absorption of each sample.
[0101] Heat aging resistance test: The test was carried out in accordance with "Polyvinyl chloride (PVC) waterproof membrane" (GB / T 12592-2011). 150mm×50mm specimens were cut out from the waterproof membrane prepared above, and each specimen was placed in a hot air aging test box for aging at an aging temperature of 80°C and an aging time of 672h. After aging, the specimens were placed in an environment with a temperature of 23°C and a relative humidity of 60% for 24h, and then the elongation at break of each specimen was tested according to the mechanical properties test method.
[0102]
[0103] Conclusion: It can be seen from the experiment that the sample of Example 1 is superior to Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 in all aspects. The high-strength PVC waterproof membrane of the present invention is superior to the general PVC waterproof membrane in terms of mechanical properties, water resistance, heat aging resistance and UV aging resistance, achieving the purpose of higher strength and better aging resistance of the prepared waterproof membrane.
[0104] Finally, it should be noted that the above is only a preferred embodiment of the present invention, but the protection scope of this application is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with the technical field within the spirit and principle of the present invention and within the technical scope disclosed in this application should be included in the protection scope of this application; in the absence of conflict, the embodiments of this application and the features in the embodiments can be combined with each other. Therefore, the protection scope of this application shall be based on the protection scope of the claims.
Claims
1. A method for preparing a high-strength PVC waterproof coiled material, characterized in that: The preparation method is: After the polyester cloth, polyvinyl chloride coiled material and glass fiber mesh cloth are arranged in the order, they are hot pressed and compounded at 145-180° C., and after cooling to room temperature, a high-strength PVC waterproof coiled material is obtained.
2. The method for preparing a high-strength PVC waterproof coiled material according to claim 1, characterized in that: The preparation method of polyvinyl chloride coil is as follows: Polyvinyl chloride, polyvinylidene fluoride, composite modified nano-silica and additives are mixed, extruded through an extruder, and calendered, pulled and rolled to prepare a polyvinyl chloride coil. During the extrusion, the mixing temperature is 70-90°C, the extrusion temperature is 170-190°C, and the screw speed is 10-30rpm.
3. The method for preparing a high-strength PVC waterproof coiled material according to claim 2, characterized in that: The preparation method of composite modified nano silicon dioxide is: The nano-silicon dioxide and toluene are mixed in a mass ratio of 1:(24-26), and ultrasonically dispersed for 20-40 minutes to obtain a nano-silicon dioxide dispersion, the nano-silicon dioxide dispersion is mixed with 3-aminopropyltriethoxysilane, and the mixture is reacted at 90-100° C. for 14-16 hours under nitrogen as a protective gas, cooled, and filtered to obtain a solid, and the solid is washed with toluene, and vacuum dried at 55-65° C. to obtain amino-modified nano-silicon dioxide; 2-bromoisobutyryl bromide and toluene are mixed in a mass ratio of (3.8-4.0):(4.1-4.3) to obtain a 2-bromoisobutyryl bromide solution, and amination nano-silica, toluene, triethylamine and the 2-bromoisobutyryl bromide solution are mixed, and the mixture is reacted at -5-0°C for 2-4 hours under nitrogen as a protective gas, and the mixture is heated to 25-30°C and the reaction is continued for 11-13 hours. After the reaction is completed, the mixture is filtered, washed with acetone and water, and vacuum dried at 55-65°C to obtain brominated nano-silica; The invention relates to a method for preparing a composite modified nano-silica. The method comprises the following steps: mixing 0.57-0.59 parts of ferric chloride hexahydrate, 4.2-4.3 parts of triphenylphosphine, 4.9-5.1 parts of brominated nano-silica, 188-190 parts of N,N-dimethylformamide and 178-180 parts of butyl acrylate, and performing ultrasonic dispersion for 14-16 minutes under closed conditions to form a mixed solution. The mixed solution is added with 1-1.1 parts of ascorbic acid, and the mixture is kept closed and reacted at 85-95° C. for 7-9 hours. The mixture is cooled, filtered, washed with tetrahydrofuran, and vacuum dried to obtain polybutyl acrylate-brominated nano-silica. The polybutyl acrylate-brominated nano-silica, triethylamine, mercaptoethylamine and tetrahydrofuran are mixed, reacted at 25-30° C. and 50-70 rpm for 7-9 hours, filtered, washed with methanol and water, and vacuum dried to obtain a composite modified nano-silica.
4. The method for preparing a high-strength PVC waterproof coiled material according to claim 2, characterized in that: The additives are composed of talc, paraffin, antioxidant, plasticizer and lead stearate.
5. The method for preparing a high-strength PVC waterproof coiled material according to claim 2, characterized in that: The mass ratio of polyvinyl chloride, polyvinylidene fluoride, composite modified nano silicon dioxide and additives is (71-73):(15-17):(7-9):(3-5).
6. The method for preparing a high-strength PVC waterproof coiled material according to claim 3, characterized in that: The mass ratio of nano-silicon dioxide dispersion to 3-aminopropyltriethoxysilane is (25-27):(1.8-2.0).
7. The method for preparing a high-strength PVC waterproof coiled material according to claim 3, characterized in that: The mass ratio of amino-modified nano-silica, toluene, triethylamine and 2-bromoisobutyryl bromide solution is 1:(12.4-12.6):(1.45-1.46):(8.0-8.2).
8. The method for preparing a high-strength PVC waterproof coiled material according to claim 3, characterized in that: The mass ratio of polybutyl acrylate-brominated nano-silica, triethylamine, mercaptoethylamine and tetrahydrofuran is (9.9-10.1):(0.14-0.16):(0.11-0.13):(177-179).
Citation Information
Patent Citations
Method for preparing silicon dioxide core-shell materials with core-shell spacing
CN104961133A
Odorless antistatic PVC composite material and preparation method thereof
CN111073174A
Photoresponsive molecularly-imprinted polymer based on magnetic mesoporous silicon nanoparticles, and preparation method and application thereof
CN111495344A
Heat-resistant flame-retardant paper-plastic composite bag and preparation method thereof
CN113981741A
Nano particle with core-shell structure as well as preparation method and application of nano particle
CN118063717A
Cited By
Novel waterproof building material and preparation method thereof
CN120137352A